1998
DOI: 10.1136/vr.143.14.394
|View full text |Cite
|
Sign up to set email alerts
|

Prolonged persistence of an epidemic Streptococcus suis strain in a closed pig population

Abstract: many sheep-raising countries. Moreover, the B melitensis Rev 1 is an effective live vaccine which is widely used for the prophylaxis of both infections (Blasco 1990). Since the hot saline antigen obtained from B ovis contains proteins and lipopolysaccharides which share epitopes with the corresponding components of B melitensis (Riezu-Boj and others 1986), it was decided to examine the extent of the cross-reactivity in the B ovis tests when testing sera from B melitensis-infected or Rev 1-vaccinated sheep. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0
3

Year Published

2001
2001
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 7 publications
1
2
0
3
Order By: Relevance
“…Pulsotype XXIV was the unique or predominant strain in several herds, being repeatedly isolated from different animals during several months or years. These results are consistent with the idea that in a closed population there is a tendency for only one strain to be established and be responsible for all or the majority of clinical cases (17,27) and confirm the ability of certain strains of S. suis to persist during prolonged periods of time in the same herd (27). All these results indicate that, together with the diversity of S. suis strains found in many herds, the existence of a prevalent or of a few prevalent clones responsible for a great proportion of clinical cases is also possible, as has been observed with other pathogens (9,28,29).…”
Section: Discussionsupporting
confidence: 81%
“…Pulsotype XXIV was the unique or predominant strain in several herds, being repeatedly isolated from different animals during several months or years. These results are consistent with the idea that in a closed population there is a tendency for only one strain to be established and be responsible for all or the majority of clinical cases (17,27) and confirm the ability of certain strains of S. suis to persist during prolonged periods of time in the same herd (27). All these results indicate that, together with the diversity of S. suis strains found in many herds, the existence of a prevalent or of a few prevalent clones responsible for a great proportion of clinical cases is also possible, as has been observed with other pathogens (9,28,29).…”
Section: Discussionsupporting
confidence: 81%
“…Also, the distribution of H. parasuis serovars has been studied in strains isolated mostly from the respiratory tract and mucosal surfaces of healthy piglets, which are probably different from those isolated from systemic sites of sick pigs (19). Recent work done with Streptococcus suis showed that isolates recovered from tonsils of healthy pigs are genetically different from isolates recovered from the brains or joints of infected pigs (21).…”
mentioning
confidence: 99%
“…The actual early mechanisms used by S. suis to colonize the host are still poorly known. The pathogen may survive in swine tonsils for long periods of time . The tonsillar lymphoid tissue is overlain by mucosal epithelium.…”
Section: Streptococcus Suis Interaction With Mucosal Barriersmentioning
confidence: 99%